ANALISIS YURIDIS MASA KERJA PADA PEGAWAI PEMERINTAH DENGAN PERJANJIAN KERJA - Adyatma, Arief Dwi (Mimbar Keadilan, 2021)
The purpose of this study is to determine the legal certainty of tenure in government employees with a work agreement. This research uses normative research methods that are oriented towards statutory and conceptual rules. Through this research, the researcher offers that the tenure of government employees with a work agreement is not explicitly regulated in Law no. 5 of 2014 concerning the State Civil Apparatus. Problems arise because of the absence of a work time limit rule in the work agreement in the State Civil Apparatus Law. This problem is in the form of unclear how long the maximum work agreement will end. As a legal state, legal certainty is very important. The government should immediately stipulate implementing regulations after the promulgation of laws and regulations so that legal certainty can be achieved. Implementing regulations such as Government Regulations, Ministerial Regulations, Presidential Decrees, or others. Legal certainty if achieved can create justice, and vice versa justice that is created also shows the existence of legal certainty. This thinking reflects good governance and the functioning of the country in good conditionKeyword: government; legal certainty, working period AbstrakTujuan penelitian ini yaitu mengetahui kepastian hukum masa kerja pada Pegawai Pemerintah Dengan Perjanjian Kerja. Penelitian ini menggunakan metode penelitian normatif yang berorientasi pada aturan perundang-undangan dan konseptual. Melalui penelitian ini peneliti menawarkan bahwa masa kerja Pegawai Pemerintah Dengan Perjanjian Kerja tidak diatur secara tegas di dalam Undang-Undang No. 5 Tahun 2014 tentang Aparatur Sipil Negara. Muncul permasalahan karena tidak adanya aturan batas waktu masa kerja dalam perjanjian kerja dalam Undang-Undang Aparatur Sipil Negara.  Permasalahan ini berupa tidak jelasnya sampai kapan maksimal perjanjian kerja ini akan berakhir. Sebagai negara hukum kepastian hukum sangatlah penting. Pemerintah seharusnya segera menetapkan peraturan pelaksana setelah diundangkannya pertaruran perundang-undangan agar kepastian hukum dapat tercapai. Peraturan pelaksana seperti Peraturan Pemerintah, Peraturan Menteri, Keppres, atau lainnya. Kepastian hukum bila dicapai dapat menciptakan keadilan, begitu juga sebaliknya keadilan yang tercipta juga memperlihatkan adanya kepastian hukum. Pemikiran ini mencerminkan pemerintahan yang baik dan guna berjalannya negara dalam keadaan baik.